INTRODUCTION TO KONSTANTIN AZADOVSKI’S "RUSSIA’S SILVER AGE IN TODAY’S RUSSIA" - Krieger, Murray (Surfaces, 2001)
In the context of the Third International Conference on Humanistic Discourse, this text introduces Konstantin Azadovski’s "Russia’s Silver Age in Today’s Russia" and reports on the central concerns that emerged in its discussion.